Adult Posterior Urethral Valve: a Case Report of the Oldest Known Patient - Hosseini, Jalil; Ansari Djafari, Anahita; Hojjati, Seyyed Ali (Archives of Men’s Health, 2021)
A posterior urethral valve (PUV) is a congenital obstructive defect of the male urethra, and sometimes maybe life threatening. The diagnosis of PUV is usually made early because of its symptoms and has rarely been diagnosed in adults for the first time in life. Here we report a rare case of an adult PUV in a 67 year-old man with 40 years history of urinary obstruction complaints with coincidence type 1 and 2 of PUV who underwent transurethral resection of the bladder neck and valve ablation. After 6 months follow-up, no evidence of urinary obstruction observed.